Percutaneous dilation tracheostomy in a patient with tracheal stent. (11th August 2021) - Fiorelli, Alfonso; Messina, Gaetana; Santini, Mario; Ferraro, Fausto
Abstract: We reported the case of a patient with obstruction of tracheal stent, deployed previously for anaplastic thyroid carcinoma. The extension of malignant stricture above and below the stent and close to the vocal folds made unfeasible the stent recanalization and/or its replacement with another longer. Thus, tracheostomy was the only option to assure ventilation. After partial air-way recanalization with rigid bronchoscope, tracheostomy cannula was inserted through the stenosis using percutaneous dilatation tracheostomy technique. Abstract : Obstruction of airway stent by tumour ingrowth is a life-threatening clinical condition, needing an emergent treatment [1, 2].